2019
DOI: 10.7150/jca.31845
|View full text |Cite
|
Sign up to set email alerts
|

CBX2 Regulates Proliferation and Apoptosis via the Phosphorylation of YAP in Hepatocellular Carcinoma

Abstract: Chromobox 2 (CBX2), a chromobox family protein, is a crucial component of the polycomb group complex: polycomb repressive complex 1 (PRC1). Research on CBX2 as an oncogene has been published in recent years. However, the connection between CBX2 and hepatocellular carcinoma (HCC) has not been studied. In this article, based on the results of immunohistochemical (IHC) staining of HCC and adjacent liver tissue microarrays, we found that high CBX2 expression is associated with poor prognosis in HCC patients. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 33 publications
2
71
0
Order By: Relevance
“…In 2014, Clermont et al (32) initially identified an oncogenic role for CBX2 through a meta-analysis of gene transcription in human cancers. Aberrantly high CBX2 levels are expressed in phenotypically diverse tumours such as breast cancer, hepatocellular cancer, oral cancer, ovarian cancer and lung cancer, for which it serves as a biomarker (21)(22)(23)(24)(25). Conversely, little is known about the expression or function of CBX2 in OSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, Clermont et al (32) initially identified an oncogenic role for CBX2 through a meta-analysis of gene transcription in human cancers. Aberrantly high CBX2 levels are expressed in phenotypically diverse tumours such as breast cancer, hepatocellular cancer, oral cancer, ovarian cancer and lung cancer, for which it serves as a biomarker (21)(22)(23)(24)(25). Conversely, little is known about the expression or function of CBX2 in OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…expressed in human tumours, including brain cancer (16), colon cancer (17), lung cancer (18) and gastric cancer (19); and CBX8 is involved in the pathogenesis of leukaemia (20). Although CBX2 has been studied in multiple cancers (21)(22)(23)(24)(25), its role in OSCC is unknown.…”
mentioning
confidence: 99%
“…Studies suggest that we can improve the clinical radiotherapy effect on LUAD by inhibiting the transcriptional regulation of HOXA10, thus prolonging survival. The other mRNA in the signature is CBX2, which is overexpressed in cancers, including breast cancer and hepatocellular carcinoma, and is significantly related to poor prognosis [24][25], indicating that its activity provides an advantages for the growth and development of cancer [26]. In addition, targeted therapy studies in non-small cell lung cancer clearly show that SMARCE1 inhibits EGFR expression, in part by modulating the level of the polycomb repressive complex component CBX2.…”
Section: Discussionmentioning
confidence: 99%
“…CBX2 is highly expressed in human HCC tissues and is associated with poor prognosis in patients with HCC [6]. CBX2 is a crucial component of the polycomb group complex, polycomb repressive complex 1 (PRC1), which is involved in human carcinogenesis [6].…”
mentioning
confidence: 99%